2016
DOI: 10.4012/dmj.2015-388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc fluoride on inhibiting dentin demineralization and collagen degradation <i>in vitro</i>: A comparison of various topical fluoride agents

Abstract: Root caries is developed because of demineralization followed by enzymatic collagen degradation. This in vitro study aimed to examine the inhibitory efficacy of ZnF2 on dentin demineralization and collagen degradation. Bovine dentin specimens were treated either with ZnF2 or HCl-acidified ZnF2 (ZnF2/HCl) and then demineralized. Anti-demineralization efficacy was assessed by TMR as mineral loss (ΔZ). The efficacy was compared with silver diammine fluoride (SDF), KF, and acidulated phosphate fluoride (APF). For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
(39 reference statements)
2
28
0
Order By: Relevance
“…An increase in the mineral density and in the hardness of the carious dentin was observed in vitro [Mei et al, 2013], which is consistent with dentin remineralization [Mei et al, 2013]. SDF also inhibits the breakdown of the exposed collagen matrix, since it inhibits matrix metalloproteinases and cysteine cathepsins [Mei et al, 2013], probably due to the high concentration of silver [Thanatvarakorn et al, 2016]. This is very important, since the collagen network provides the scaffold for the new remineralization cores.…”
Section: Discussionsupporting
confidence: 57%
“…An increase in the mineral density and in the hardness of the carious dentin was observed in vitro [Mei et al, 2013], which is consistent with dentin remineralization [Mei et al, 2013]. SDF also inhibits the breakdown of the exposed collagen matrix, since it inhibits matrix metalloproteinases and cysteine cathepsins [Mei et al, 2013], probably due to the high concentration of silver [Thanatvarakorn et al, 2016]. This is very important, since the collagen network provides the scaffold for the new remineralization cores.…”
Section: Discussionsupporting
confidence: 57%
“…It has been previously shown that high levels of ZnCl 2 (3.33 mg/mL, ∼ 22 m M ) could significantly inhibit the MMP-induced degradation of DOM [Osorio et al, 2011a], and when doped in adhesive resin formulations, no adverse effect on the immediate bond strength to dentin was observed [Osorio et al, 2011b;Toledano et al, 2012aToledano et al, , b, 2016Thanatvarakorn et al, 2016]. The inhibition mechanism has been attributed to changes in the MMP protein configuration due to excess zinc binding, or to the formation of a zinc-hydroxide bridge blocking the catalytic site of the MMPs [Tezvergil-Mutluay et al, 2010].…”
mentioning
confidence: 99%
“…Accordingly, they increased dentin resistance to bacterial acids, led to reduction in LD and mineral loss. Zinc, fluoride and calcium in the Biounion Nanofiller of CS were able to demonstrate inhibitory effects on dental hard tissue demineralization 10,25,35,36) and enhance remineralization [37][38][39] , in addition to the ability of fluoride to form fluorapatite, which decreases crystal solubility and makes it more resistant to acid attack 40) . Future studies including SEM/EPMA analysis of both materials are essential to understand more about the exact constituents of the formed precipitates.…”
Section: Discussionmentioning
confidence: 99%
“…After demineralization by artificial biofilm formation, the specimens were cut into approximately 220 μm thick sections using a low-speed diamond saw and then immediately immersed in a 70% aqueous glycerin solution to prevent lesion shrinkage 25) . To perform TMR imaging, the excess glycerin was removed from the sections, then placed on an X-ray glass plate (High Precision Photo Plate, Konica Minolta Photo, Tokyo, Japan), with a 15-step aluminum step wedge.…”
Section: Tmr Analysismentioning
confidence: 99%